Fatty Acid Derivatives Isolated from the Oil of Persea americana (Avocado) Protects against Neomycin-Induced Hair Cell Damage - SeonJu Park; Seo Yule Jeong; Youn Hee Nam; Jun Hyung Park; Isabel Rodriguez; Ji Heon Shim; Tamanna Yasmin; Hee Jae Kwak; Youngse Oh; Mira Oh; Kye Wan Lee; Jung Suk Lee; et al. (Plants, 2021)
Avocado oil is beneficial to human health and has been reported to have beneficial effects on sensorineural hearing loss (SNHL). However, the compounds in avocado oil that affect SNHL have not been identified. In this study, we identified 20 compounds from avocado oil, including two new and 18 known fatty acid derivatives, using extensive spectroscopic analysis. The efficacy of the isolated compounds for improving SNHL was investigated in an ototoxic zebrafish model. The two new compounds, namely (2R,4R,6Z)-1,2,4-trihydroxynonadec-6-ene and (2R,4R)-1,2,4-trihydroxyheptadecadi-14,16-ene (compounds 1 and 2), as well as compounds 7, 9, 14, 17 and 19 showed significant improvement in damaged hair cells in toxic zebrafish. These results led to the conclusion that compounds from avocado oil as well as oil itself have a regenerative effect on damaged otic hair cells in ototoxic zebrafish.